Sufism and social cohesion: The role of Hizib Nahdlatul Wathan Tariqa in pluralistic religious life in East Lombok - Rasyad, Abdul; Tohri, Ahmad; Basri, Hasan; Chaer, Hasanuddin (Program Pascasarjana Universitas Negeri Yogyakarta, 2025)
Tariqa, within the framework of Sufism, refers to a system of religious thought and practice cultivated and exemplified by adherents of Sufi orders (tarekat) who embody a pluralistic orientation. This study seeks to elucidate the evolution of a diversity-orientated mentality embedded in tariqa (tasawuf) practices in East Lombok during the New Order era. Employing a historical research approach, this study adopts the established stages of historical inquiry is heuristics, source criticism, interpretation, and historiography. The findings indicate that the development of tariqa in East Lombok constitutes a long-standing historical process, rooted in the introduction of Islam to the region in the 15th and 16th centuries. This development has been consistently preserved as an integral element of the religious fabric of East Lombok society. The mentality of diversity has been culturally nurtured through a sustained and profound relationship between spiritual teachers (murshid) and their disciples within tarekat institutions. During the New Order period, the transformation of tariqa adherents into a community committed to fostering a culture of inclusivity and social cohesion was notably evident. Remarkably, the region experienced no communal conflict throughout the era, contributing to the formation of a harmonious society. This study aspires to contribute meaningfully to scholarly discourse on tariqa practices that embody tolerance and serve as exemplary models within pluralistic societies.